Production of herbal kombucha with agarwood (Aquilaria crassna Pierre ex Lec.) leaves and its biological properties - Suwanposri, A.; Khamphinit, W.; Sonthichai, P.; Maliyam, R.; Charoensook, K.; Boonna, S. (International Journal of Agricultural Technology, 2025)
Herbal kombucha from roselle (Hibiscus sabdariffa L.) and peppermint (Mentha × piperita) mixed with agarwood leaves (Aquilaria crassna Pierre ex Lec.) was produced and its biological activity was analyzed. After 14 days of static fermentation, it was found that all kombucha formulations had acetic acid levels ranging from 0.28±0.01% to 0.41±0.00%, alcohol levels from 1.07±0.15% to 1.32±0.08%, and total phenolic content from 3,577.78±96.86 to 8,066.67±905.13 µg/mL. DPPH scavenging activity ranged from 56.02±0.11% to 84.91±0.84%. The population of acetic acid bacteria, lactic acid bacteria, and yeast ranged from 7.75±0.05 to 7.97±0.01 log CFU/mL, 7.63±0.07 to 7.98±0.02 log CFU/mL, and 7.59±0.04 to 7.89±0.017 log CFU/mL, respectively, which meet the standards of the Food and Drug Administration. Kombucha made from roselle and roselle mixed with agarwood leaves at concentrations of 0.01% and 0.05% inhibited Staphylococcus aureus and Escherichia coli. Additionally, sensory evaluation scores for overall acceptability were in the range of like slightly to like moderately. It indicated that the production of herbal kombucha with agarwood leaves couble be suitable for commercial development.